2021
DOI: 10.1016/j.jvscit.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Superselective carotid body tumor embolization with platinum-based coils

Abstract: Resection of Shamblin II and III carotid body tumors can be challenging owing to the potential for significant blood loss. Prophylactic use of liquid embolic agents poses a risk of inflammatory reactions and nontarget embolization. On the other hand, coil embolization has traditionally been limited to cases involving external carotid artery sacrifice. Herein we demonstrate that superselective targeting of tumor-feeding vessels using platinum based, fully detachable packing coils is effective at sustained devas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Regarding PE, recent debates have arisen, with some authors [16][17][18] advocating for its use due to reported reductions in blood loss and postoperative hematomas. Conversely, others [19][20][21][22] have highlighted a potential association with longer hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PE, recent debates have arisen, with some authors [16][17][18] advocating for its use due to reported reductions in blood loss and postoperative hematomas. Conversely, others [19][20][21][22] have highlighted a potential association with longer hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative approaches to embolization include platinum-based, fully detachable packing coils. 12 We prefer intra-arterial Onyx injection for embolization when the number of feeders is limited (fewer than five to six). If too many feeders are present, we also use direct stick embolization with preference for an N -butyl cyanoacrylate with ethiodol 25% mixture, because Onyx can cause breakage of the hub of the needle used to puncture the lesion due to a reaction with dimethyl sulfoxide.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐embolization of CBTs can be helpful in decreasing blood loss and reducing risk for cranial nerve deficits by reducing the number of feeding arteries to the vessel 1,2 . However, embolization presents with risks, including local inflammation, neural damage, and a 3% risk of downstream emboli 7,8 . Timing of pre‐embolization before surgical resection is also important to consider due to the risk of tumor revascularization prior to resection 9 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 However, embolization presents with risks, including local inflammation, neural damage, and a 3% risk of downstream emboli. 7 , 8 Timing of pre‐embolization before surgical resection is also important to consider due to the risk of tumor revascularization prior to resection. 9 Other studies found no significant differences in EBL from pre‐embolization.…”
Section: Introductionmentioning
confidence: 99%